An Analysis of Seventh-Grade Students’ Critical Thinking Skills in Solving Triangle-Based Word Problems - Herdiana, Andre; Usmiyati, Uum (Papanda Publisher, 2024)
This study aims to analyze the critical thinking skills of seventh-grade students in solving word problems involving triangle concepts. Employing a qualitative descriptive method, the research was conducted at SMP Negeri 3 Sukadana with three students representing high, moderate, and low performance levels. Data were collected through essay-based test items and follow-up interviews, focusing on five indicators of critical thinking: elementary clarification, basic support, inference, advanced clarification, and strategies and tactics. The findings revealed that students experienced difficulties across all indicators, particularly in integrating strategies and making valid conclusions. Average scores for each indicator demonstrated that students’ critical thinking skills remain at a developing level. This suggests the need for instructional interventions that explicitly foster reasoning, analysis, and reflective thinking. The study highlights the importance of contextual and open-ended problem-solving in developing students’ mathematical understanding and higher-order thinking skills.